2020
DOI: 10.1111/fare.12528
|View full text |Cite
|
Sign up to set email alerts
|

Parenting in a Pandemic: Work–Family Arrangements, Well‐Being, and Intimate Relationships Among Adoptive Parents

Abstract: The COVID‐19 pandemic presents unforeseen challenges to families. This mixed‐methods study aimed to address how 89 adoptive parents (lesbian, gay, heterosexual) with school‐age children are navigating a major public health crisis with social, economic, and mental health consequences. Specifically of interest were adoptive parents' worries and concerns; work–family arrangements; and mental, physical, and relational health, in the context of the pandemic and associated quarantine. Findings revealed that 70% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(122 citation statements)
references
References 44 publications
(49 reference statements)
6
114
0
2
Order By: Relevance
“…Many parents of school age children found themselves balancing working from home while caring for and educating their children (Brown et al, 2020;Goldberg et al, 2021;Griffith, 2020;Hiraoka & Tomoda, 2020). However, this balancing of new roles may be different for father-child and mother-child relationships.…”
Section: Parent-child Relationships and Covid-19 Pandemicmentioning
confidence: 99%
“…Many parents of school age children found themselves balancing working from home while caring for and educating their children (Brown et al, 2020;Goldberg et al, 2021;Griffith, 2020;Hiraoka & Tomoda, 2020). However, this balancing of new roles may be different for father-child and mother-child relationships.…”
Section: Parent-child Relationships and Covid-19 Pandemicmentioning
confidence: 99%
“…In their sample of adoptive parents during COVID-19, Goldberg et al (2021) also found that parents frequently reported declines in mental health, particularly women partnered with women, who also had the lowest average income in the sample. Many of these parents who reported declining mental health explained this in relation to working and homeschooling constantly, uncertainty about the future, lack of time to themselves, social isolation, and other stressors.…”
Section: Discussionmentioning
confidence: 93%
“…The COVID-19 pandemic significantly impacted individuals, families, and communities. Within the context of the United States, many parents experienced changes in employment such as job loss or a transition to remote work, while children moved to remote schooling, and overall stress levels increased (Brown et al, 2020;Goldberg et al, 2021).…”
mentioning
confidence: 99%
“…Turning to participants’ concerns regarding child outcomes, child welfare workers and therapists worried about the academic functioning and progress of children in foster care, who may not only be at greater risk for academic difficulties, but whose access to special educational resources may be limited during the pandemic (Goldberg et al, 2021). If such resources are provided, they are often done so online, which can be less engaging for youth with ADHD and other executive functioning difficulties (Becker et al, 2020; Goldberg et al, 2021). Likewise, children in foster care may struggle with isolation and exacerbated emotional and behavioral challenges—which may be especially difficult to address given the virtual nature of most therapies during the pandemic (Racine et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 and associated physical distancing/safety behavior requirements may result in decreased access to educational and mental health professionals. If and when such supports are provided virtually, they may not be as effective: Children with ADHD and children receiving special education services, for example, have been found to struggle more intensely with remote learning during COVID-19 (Becker et al, 2020; Goldberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%